Determinants of Foreign Direct Investment (FDI) in Java Island: Strategic Implications for Regional Development - Wibowo, Arief Nugroho; Subiyantoro, Heru; Sugiyanto; Pujiastuti (PT Maju Malaqbi Makkarana, 2025)
This study aims to analyze the influence of infrastructure, labor costs, market size, and governance on Foreign Direct Investment (FDI) in Indonesia during the 2016–2017 period. Using a quantitative approach and annual secondary data, multiple linear regression analysis was conducted through SPSS 26. The findings indicate that while infrastructure and governance demonstrated relatively stable conditions, labor costs significantly fluctuated and appeared to have a potential inverse relationship with FDI inflows. However, the statistical significance during this period was limited due to the small data sample, suggesting the need for further longitudinal data to draw firmer conclusions. The analysis provides an early insight into how these structural factors might shape FDI performance in the post-global financial recovery phase.